Large improvement in trap level and space charge distribution of polypropylene by enhancing the crystalline − amorphous interface effect in blends. Issue 4 (2nd February 2016) - Dang, Bin; He, Jinliang; Hu, Jun; Zhou, Yao
Abstract : PP/EOC blends have more shallow traps at boundaries of spherulites than PP and PP/PEC blends. The shallow traps can improve the transportation of charges. Abstract: The accumulation of space charge in high voltage direct current cable will bring the insulation to failure; the addition of nanoparticles can markedly improve the space charge distribution characteristics inside the cable insulation, but particle agglomeration and cavitation lead to difficulty in controlling the properties of nanocomposites. In this paper, polypropylene (PP)/propylene‐ethylene copolymer (PEC) and PP/ethylene‐octene copolymer (EOC) blends were prepared by mechanical blending in order to improve both mechanical properties and space charge distribution. Dynamic mechanical thermal analysis shows that both blends have excellent mechanical properties for recyclable power cable. Pulsed electro‐acoustic and thermally stimulated depolarization current tests illustrate that PP/EOC blends significantly decrease space charge accumulation and remarkably increase the trap density in the bulk compared with PP and PP/PEC blends. The increase of the trap density in PP/EOC blends can be explained as the result of the shallow traps introduced by the crystalline − amorphous interface existing in the boundaries of spherulites. The shallow traps can act as hopping sites to improve the transportation of space charges. © 2016 Society of Chemical Industry